THE RELATIONSHIP BETWEEN STRESS LEVELS, NUTRITIONAL STATUS, AND SLEEP QUALITY WITH THE MENSTRUAL CYCLE - Shandrya Malaciano; Muhamad Taswin; Sari Wahyuni; Ratnaningsih Dewi Astuti; Rosyati Pastuty (Indonesian Global Journal Of Medical Research and Development, 2025)
Background: Menstruation is a natural process of sexual maturity that begins during puberty, with a normal cycle ranging from 21 to 35 days. However, menstrual disorders such as polymenorrhea, oligomenorrhea and amenorrhea can occur, and if untreated, may lead to serious long-term health issues including infertility, cervical cancer, and breast cancer. This study aimed to analyze the relationship between stress levels, nutritional status, and sleep quality with menstrual cycle disorders. Method: The research applied an analytical survey with a cross-sectional design, involving 95 respondents selected using a total sampling method. Data collection was conducted using several instruments, including a menstrual cycle disorder questionnaire, Depression Anxiety Stress Scales (DASS 42), Body Mass Index (BMI) questionnaire, and Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Chi-Square test in SPSS version 26.Results: The results showed that 62 respondents (65.3%) experienced abnormal menstrual cycles, while 33 (34.7%) had normal cycles. Stress levels were significantly associated with menstrual disorders (p = 0.001 ≤ 0.05). Furthermore, 54 respondents (56.8%) had abnormal nutritional status (BMI < 18.5 or BMI ≥ 25), with a significant relationship to menstrual disorders (p = 0.006 ≤ 0.05).Similarly, 53 respondents (55.8%) reported poor sleep quality (PSQI < 5), which also showed a significant association (p = 0.010 ≤ 0.05). Conclusion: his study found a significant relationship between stress levels, nutritional status, and sleep quality with menstrual cycle disorders among midwifery students.